Innovative Energy Technologies for Powering Buildings - Nicolae Badea; George Vlad Badea; Andreia Podasca (International Journal of Architectural Engineering Technology, 2020)
This paper makes a technical analysis of the methods that can be used to provide Energy to Residential Buildings. The paper firstly describes the legislative framework for increasing the efficiency in the building sector and building certification. The key for improving the energy efficiency of buildings is ‘Nearly Zero-Energy Buildings(nZEB)‘. The main research in nZEB is described in section three and the technologies for increasing the energy performance of buildings, in summary, are presented in section four. A case study of the integration of renewable sources in the energy supply of residential buildings describes the calculation methodology of required energy, the specific consumption, and energy performance of building after inclusion of renewable energy for powering the building. The results of this analysis show that the energy uses in nZEB buildings are influenced by the building location, their architecture, energy system design, and level of renewable energy production.